2021
DOI: 10.1063/9.0000190
|View full text |Cite
|
Sign up to set email alerts
|

The impact of solvent tanδ on the magnetic characteristics of nanostructured NiZn-ferrite film deposited by microwave-assisted solvothermal technique

Abstract: Paper published as part of the special topic on 65th Annual Conference on Magnetism and Magnetic Materials ARTICLES YOU MAY BE INTERESTED IN W thickness dependence of spin Hall effect for (W/Hf)-multilayer electrode/CoFeB/MgO systems with flat and highly (100) oriented MgO layer AIP Advances 11, 025007 (2021);

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…This result is, however, not possible through synthesis techniques involving conventional heating processes. In addition, Kahmei et al have shown that the heating rate in a microwave-assisted process can be used to modulate the position of cationic sites in complex oxide nanostructures, thereby altering the magnetic anisotropy in a material [31]. The uniform heating of the solution in the MAS process, as well as the reducing character of ethylene glycol, leads to the formation of cobalt monoxide crystallites with a fairly narrow size distribution.…”
Section: Sem-edsmentioning
confidence: 99%
“…This result is, however, not possible through synthesis techniques involving conventional heating processes. In addition, Kahmei et al have shown that the heating rate in a microwave-assisted process can be used to modulate the position of cationic sites in complex oxide nanostructures, thereby altering the magnetic anisotropy in a material [31]. The uniform heating of the solution in the MAS process, as well as the reducing character of ethylene glycol, leads to the formation of cobalt monoxide crystallites with a fairly narrow size distribution.…”
Section: Sem-edsmentioning
confidence: 99%
“…Recently, we used the non-hazardous combination of metal acetylacetonates and alcohols to grow high-quality thin films of ferrites such as Zn-ferrite, MnZn-ferrite, and Ni-ferrite 15,16,[23][24][25] films by MASS. It was a counter-intuitive synthetic approach to use a mixture of the poorly microwave-absorbent (tan d E 0.1) but high-boiling-point (b.p.)…”
Section: Introductionmentioning
confidence: 99%
“…This choice of solvent(s) led to far-from-equilibrium cationic arrangements in the ferrite nanocrystallites, and thus unforeseen magnetic properties of technological value, pertinent to RF and mm-wave electronic devices. 15,23,25,26 Therefore, a thorough understanding of the reaction pathways involved in the formation of such oxides became essential not only to ensure repeatable and scalable deposition, but also to control the physical and chemical attributes of these nano-ferrites. Furthermore, in a sensitive set-up such as in the thin-film industry, it is very important to have knowledge of toxicity, if any, of reaction by-products, so as to ensure their safe disposal, and of the reactivity of the evolved gaseous by-products, so as to minimize the damage caused by them.…”
Section: Introductionmentioning
confidence: 99%